2011
DOI: 10.1111/j.1537-2995.2011.03286.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cells from poor and good mobilizers are qualitatively equivalent

Abstract: Background Marrow damage from chemo- and radiation therapies has been suggested to affect quality and quantity of Hematopoietic stem cell (HSC) products. We tested the hypothesis that CD34+ cells (HSC) from low mobilizers are qualitatively inferior to HSC from high mobilizers. Materials and Methods HSC quality was defined by proportion of primitive HSC subsets (CD34+CD38−, CD34+HLA-DR− and CD34+ in G0 stage of cell cycle), the proportion of HSCs that express CXCR4 and CD26 homing proteins and days, to neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…11 With regard to frequencies of CD341CD38-stem cell subsets our findings are in line with a recently published study analyzing grafts from 139 NHL patients after mobilization with G-CSF alone. 31 This study shows that stem cell grafts contained a relatively high amount of primitive CD341CD38-cells (52%-55%). These findings are comparable to our results detected in the G group (mean percentage of MPPs, 49.2%).…”
Section: Discussionmentioning
confidence: 66%
“…11 With regard to frequencies of CD341CD38-stem cell subsets our findings are in line with a recently published study analyzing grafts from 139 NHL patients after mobilization with G-CSF alone. 31 This study shows that stem cell grafts contained a relatively high amount of primitive CD341CD38-cells (52%-55%). These findings are comparable to our results detected in the G group (mean percentage of MPPs, 49.2%).…”
Section: Discussionmentioning
confidence: 66%
“…Jiang and colleagues have reported that mobilization capacity affects time to PLT engraftment and is significantly shorter in high mobilizers (CD34+ yield > 5 × 10 6 /kg at first leukapheresis) compared to low mobilizers (CD34+ cell yield < 3 × 10 6 /kg at first leukapheresis). Contrary to these findings, despite fewer numbers of low mobilizers in the Nivestim group compared to the Neupogen group and similar numbers of high mobilizers, a delay in time to PLT engraftment in the Nivestim group was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A critical point is whether the grafts collected from poor mobilizers are intrinsically different than those collected from standard mobilizers except for poorer yield of CD34+ cells. A recent study suggests that quality of hematopoietic stem cells is comparable in good mobilizers compared to poor mobilizers 33 . Apparently, this issue can be answered only through a randomized mobilization study.…”
Section: Discussionmentioning
confidence: 99%